Ruxolitinib for Treatment of Steroid-Refractory Graft-versus-Host Disease: Real-World Data from Chinese Patients - Wei C; Zhang X; Liang D; Yang J; Du J; Yue C; Deng L (Dove Medical Press, 2021)
Cong Wei,1,* Xiaoting Zhang,1,* Dan Liang,1 Jilong Yang,1 Jingwen Du,1 Chunyan Yue,1 Lan Deng1,2 1Department of Hematology, Zhujiang Hospital, Southern Medical University, Guangzhou, 510280, People's Republic of China; 2Department of Hematology, Shanghai Ninth People's Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200011, People's Republic of China*These authors contributed equally to this workCorrespondence: Lan DengDepartment of Hematology, Shanghai Ninth People's Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200011, People's Republic of ChinaTel +86 13724862939Email denglan_76@126.comChunyan YueDepartment of Hematology, Zhujiang Hospital, Southern Medical University, Guangzhou, 510280, People's Republic of ChinaTel +86 15521117300Email doctor_yy@126.comBackground: Graft-versus-host disease (GVHD) is a main complication following allogeneic hematopoietic stem cell transplantation and is a leading cause of non-relapse-related death. Unsatisfactory response to standard first-line therapy with glucocorticoids is a predictor of a poor prognosis in patients with GVHD. Ruxolitinib is a selective Janus kinases 1/2 inhibitor which has been shown to control acute (a) and chronic (c) GVHD while maintaining graft-versus-tumor effects.Objective: This study aims to evaluate the efficacy and safety of ruxolitinib in the treatment of steroid-refractory GVHD (SR-GVHD) in a population of Chinese patients.Methods: We report the results of 55 patients, including 23 patients with aGVHD and 32 patients with cGVHD, who were treated with ruxolitinib as salvage therapy between August, 2017 and December, 2020.Results: In patients with aGVHD, the overall response rate (ORR) was 86.9%, and the 1-year overall survival (OS) was 82.6% (95% CI, 67.1- 98.1%). The 1-year OS was significantly improved in responders than in non-responders (90.0% vs 33.3%, P=0.004). In patients with cGVHD, the ORR was 78.1%, and the 1-year OS was 81.3% (95% CI, 67.8- 94.8%). There was no significant difference in the 1-year OS between responders and non-responders (84.0% vs 71.4%, P=0.327). Cytopenia, cytomegalovirus-reactivation and infections were common adverse events, particularly in patients with aGVHD.Conclusion: Our real-world data from Chinese patients further confirm that ruxolitinib is a safe and effective treatment for SR-GVHD.Keywords: ruxolitinib, allogeneic hematopoietic stem cell transplantation, graft-versus-host disease, steroid-refractory